Electronic Commerce: Reality & Challenges - عبدالسلام, عائشة (Dirasat in Economics and Business, 2011)
This paper aims at highlighting the concept of Electronic commerce (EC), and its economic importance This will be followed by describing this concept within the global arena, focusing on the Arab and Libya contexts. Finally, the study explains the important challenges that face the development of (EC) in the Arab world and Libya. This paper suggests some suitable means that might guarantee and advanced pace of (EC) in this specific area.